Advances in treatments of patients with classical and emergent neurological toxicities of anticancer agents - Bompaire, F.; Birzu, C.; Bihan, K.; Desestret, V.; Fargeot, G.; Farina, A.; Joubert, B.; Leclercq, D.; Nichelli, L.; Picca, A.; Tafani, C.; Weiss, N.; et al. (Revue neurologique, 2023)
•The continuous development of new oncological treatments have led to the emergence of new neurological side effects.•The neurological side effects of oncological treatments can be life threatening or can impair greatly the quality of life; their management should be performed by specialized teams.•Classical oncological treatments as brain radiotherapy are subjected to toxicity mitigating strategies and improvement of neurological complication diagnosis and management.•Innovating oncological treatments as the immune checkpoint inhibitors and the CAR-T cells are responsible for immune-mediated toxicities.•Molecularly targeted therapies represent an expanding class associated to both cytotoxic and immune-mediated adverse events. The neurotoxicity associated to the anticancer treatments has received a growing body of interest in the recent years. The development of innovating therapies over the last 20years has led to the emergence of new toxicities. Their diagnosis and management can be challenging in the clinical practice and further research is warranted to improve the understanding of their pathogenic mechanisms. Conventional treatments as radiation therapy and chemotherapy are associated to well-known and under exploration emerging central nervous system (CNS) and peripheral nervous system (PNS) toxicities. The identification of the risk factors and a better understanding of their pathogeny through a “bench to bedside and back again” approach, are the first steps towards the development of toxicity mitigation strategies. New imaging techniques and biological explorations are invaluable for their diagnosis. Immunotherapies have changed the cancer treatment paradigm from tumor cell centered to immune modulation towards an efficient anticancer immune response. The use of the immune checkpoints inhibitors (ICI) and CAR-T cells (chimeric antigen receptor) lead to an increase in the incidence of immune-mediated toxicities and new challenges in the neurological patient's management. The neurological ICI related adverse events (n-irAE) are rare but potentially severe and may present with both CNS and PNS involvement. The most frequent and well characterized, from a clinical and biological standpoint, are the PNS phenotypes: myositis and polyradiculoneuropathy, but the knowledge on CNS phenotypes and their treatments is expanding. The n-irAE management requires a good balance between dampening the autoimmune toxicity without impairing the anticancer immunity. The adoptive cell therapies as CAR-T cells, a promising anticancer strategy, trigger cellular activation and massive production of proinflammatory cytokines inducing frequent and sometime severe toxicity known as cytokine release syndrome and immune effector cell-associated neurologic syndrome. Their management requires a close partnership between oncologist-hematologists, neurologists, and intensivists. The oncological patient's management requires a multidisciplinary clinical team (oncologist, neurologist and paramedical) as well as a research team leading towards a better understanding and a better management of the neurological toxicities.